A lateral cephalometric and arch width Study between class II division 1 malocclusion and Class II division 2 malocclusion (A comparative study) (Mustansiria Dental Journal, 2018)
Background: the purpose of this retrospective study was to compare somecraniofacral cephalometric measurements and arch width dimensions betweensubjects with class II division 1 and class II division 2 malocclusion in Iraqipopulation.Materials and methods: 60 digital true lateral cephalometric radiographs 30 for classII division 1 and 30 for class II division 2 subjects (15 males, 15 females for eachgroup ) were selected from the files of the patients attending the orthodontic clinicin the college of dentistry, university of Baghdad with an over jet more than 6 mmand class II molar and canine relation. Also for each group a study model weretake to measure the arch width for both upper and lower arches. The inter molar,inter premolar and inter canine measurements were carried out on study models.The radio graphs were digitized by using the Auto CAD program in the personalcomputer all the data compared by independent t- test.Results and conclusions: For the dental arch width measurements the statisticallysignificant difference was found between the mandibular inter canine width andmaxillary inter molar width. The cephalometric results that class II division 1showed a retrognathic mandible, and this due to the difference in SNB anglebetween the two groups, the class II division 2 subjects had anterior position of themandible relative to the cranial base, more concave profile, great posterior faceheight, horizontal growth, the mandibular inclination is interiorly, more deep bite,and reduction in the mandibular inter canine width and maxillary inter molarwidth .